Unfinished Promises in Federal Nepal: Provincial Disparities, Household Realities, and the Quest for Human Development - Khanal, Kashi Nath (Interdisciplinary Journal of Management and Social Sciences, 2025)
This paper commences a comprehensive and deeply analytical examination of the profound socio-economic disparities that unambiguously define Nepal’s contemporary provincial landscape. It critically assesses the complex and powerful relationship between the economic capacity of households and the realized human development of their communities. Drawing upon the rich, granular dataset of the Nepal Living Standards Survey IV (NLSS-IV, 2022/23) for household expenditure and provincial Human Development Index (HDI) data from the Nepal Statistical Yearbook 2023, this paper offers a statistically rigorous and deeply cultivated analysis of Nepal’s federal promise. The study employs a mixed-method quantitative approach, including detailed descriptive statistics, Analysis of Variance (ANOVA), and simple linear regression, to meticulously explore these dynamics. The findings shade a vivid and unsettling alienated picture of a nation. Descriptive analysis showcases a vast economic gulf, where the per capita annual household expenditure in the prosperous Bagmati Province overshadows the tragically insufficient resources available in Madhesh, Karnali and Sudurpaschim Provinces. The results from analysis of variance decisively confirm that these provincial differences are statistically significant, revealing a pattern of systemic, rather than random, inequality. The cornerstone of the analysis, a simple linear regression model, demonstrates an overwhelmingly strong, positive, and statistically significant correlation between per capita expenditure and the provincial Human Development Index. The model explains an exceptional variance, suggesting with stunning clarity that economic resources are the primary driver of human development outcomes at the provincial level. Grounded in Amartya Sen’s powerful Capability Approach, the discussion argues that the central obstacle to equitable human development in Nepal’s lagging provinces is not primarily an inefficient conversion of resources into well-being, but rather a fundamental, crippling lack of resources to convert in the first place. This paper fervently posits that Nepal’s federal project must urgently address economic disparities through targeted fiscal federalism, strategic infrastructure investment, and a profound commitment to human capital development in its most forgotten corners.